Information photonics : fundamentals, technologies, and applications - Datta, Asit Kumar
"This book gives the reader a comprehensive idea about how photons work in an information era for communication and computation in day-to-day and strategic applications. It introduces post-graduate students, researchers, engineers, and scientists, to photonic information processing technologies as applied in various fields. It gets into the insight of the concepts of photonic information processing as a system, the photonic devices required, and applications in the fields of communication, computation, and intelligent pattern recognition."--